Handbook of research on AI-based technologies and applications in the era of the metaverse - Khang, Alex; Shah, Vrushank Manharlal 1985-; Rani, Sita (Advances in computational intelligence and robotics (ACIR), 2023)
AI-based technologies and applications in the era of the Metaverse discusses essential components of the metaverse ecosystem such as concepts, methodologies, technologies, modeling, designs, statistics, implementation, and maintenance. Covering key topics such as machine learning, deep learning, quantum computing, and blockchain, this premier reference source is ideal for computer scientists, industry professionals, researchers, academicians, scholars, practitioners, instructors, and students